2019
DOI: 10.1097/ogx.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Diazepam for the Treatment of Pelvic Floor Hypertonic Disorder: A Double-blind, Randomized, Placebo-Controlled Trial

Abstract: (Abstracted from Female Pelvic Med Reconstr Surg 2019;25:76–81) Pelvic floor hypertonic disorder is a neuromuscular condition that causes involuntary spasms of the levator ani muscles, resulting in reproducible pelvic pain during vaginal intercourse or internal pelvic examination. It may act as a primary pain generator, a singular component of pelvic pain, or cause bladder or bowel dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In an RCT by Crisp et al,43 in which patients with hypertonic pelvic floor muscles were treated with 10-mg diazepam suppositories or placebo nightly for 28 days, diazepam failed to produce a difference in pelvic floor tone, pain, or sexual function. Holland et al44 treated 35 patients with pelvic pain in the same manner, and again diazepam 10-mg suppositories failed to improve pain or other symptoms. In a retrospective study by Rogalski et al,45 26 patients were treated with high-tone pelvic floor dysfunction (80.7% had vestibulodynia) with 10-mg diazepam suppositories nightly for 30 days, in addition to pelvic floor physical therapy and intramuscular trigger point injections.…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT by Crisp et al,43 in which patients with hypertonic pelvic floor muscles were treated with 10-mg diazepam suppositories or placebo nightly for 28 days, diazepam failed to produce a difference in pelvic floor tone, pain, or sexual function. Holland et al44 treated 35 patients with pelvic pain in the same manner, and again diazepam 10-mg suppositories failed to improve pain or other symptoms. In a retrospective study by Rogalski et al,45 26 patients were treated with high-tone pelvic floor dysfunction (80.7% had vestibulodynia) with 10-mg diazepam suppositories nightly for 30 days, in addition to pelvic floor physical therapy and intramuscular trigger point injections.…”
Section: Discussionmentioning
confidence: 99%
“…Diazepam vaginal suppositories and tablets have been prescribed to treat vulvodynia 18 and vulvar pain related to hypertonic pelvic floor muscles. 11,[43][44][45] Studies conducted on the use of vaginal diazepam have targeted women with pelvic pain related to hypertonic pelvic floor muscles [46][47][48] but not specifically vulvodynia. There were 2 small-sample double-blind RCTs 46,47 of vaginal diazepam for hypertonic pelvic floor dysfunction that showed no reduction in vulvar pain.…”
Section: Diazepam Vaginal Suppositories and Tabletsmentioning
confidence: 99%
“…11,[43][44][45] Studies conducted on the use of vaginal diazepam have targeted women with pelvic pain related to hypertonic pelvic floor muscles [46][47][48] but not specifically vulvodynia. There were 2 small-sample double-blind RCTs 46,47 of vaginal diazepam for hypertonic pelvic floor dysfunction that showed no reduction in vulvar pain. A third double-blinded RCT 48 of diazepam with intravaginal transcutaneous electrical nerve stimulation (TENS) versus placebo with TENS for PV also showed no reduction in vulvar pain but did show a significant reduction in dyspareunia.…”
Section: Diazepam Vaginal Suppositories and Tabletsmentioning
confidence: 99%
“…Studies regarding their efficacy for pelvic hypertonicity and/or dysfunction are limited and show mixed results. 26 , 51 , 64 , 86 A study of 49 randomized women (25 in the diazepam arm and 24 in the placebo arm) showed no difference in scores between the treatment groups after 4 weeks (50 vs 39 mm, for diazepam and placebo, respectively; P = 0.36). 51 Contrastingly, a study of 21 women taking diazepam for a month showed a decrease from 5.9 to 2.2 in the average pain score.…”
Section: Treatmentmentioning
confidence: 99%
“… 26 , 51 , 64 , 86 A study of 49 randomized women (25 in the diazepam arm and 24 in the placebo arm) showed no difference in scores between the treatment groups after 4 weeks (50 vs 39 mm, for diazepam and placebo, respectively; P = 0.36). 51 Contrastingly, a study of 21 women taking diazepam for a month showed a decrease from 5.9 to 2.2 in the average pain score. The small sample size of this study limits any widespread conclusions.…”
Section: Treatmentmentioning
confidence: 99%